Incarceration, HIV Risk–Related Behaviors, and Partner Characteristics Among Heterosexual Men at Increased Risk of HIV Infection, 20 US Cities. (May 2019) - Wise, Akilah; Finlayson, Teresa; Sionean, Catlainn; Paz-Bailey, Gabriela
Objectives: The effect of incarceration on HIV risk–related behaviors among at-risk heterosexual men is understudied. The objective of our study was to examine the association between incarceration and HIV risk–related behaviors among a sample of predominantly non-Hispanic black and Hispanic heterosexual men residing in urban areas in the United States with a high prevalence of AIDS. Methods: We analyzed data from the 2013 National HIV Behavioral Surveillance system on 5321 at-risk heterosexual men using log-linked Poisson regression models, adjusted for demographic characteristics and clustered on city. Results: Of 5321 men, 1417 (26.6%) had recently been incarcerated (in the past 12 months), 2781 (52.3%) had ever been incarcerated but not in the past 12 months, and 1123 (21.1%) had never been incarcerated. Recent incarceration was associated with multiple casual female sexual partners (adjusted prevalence ratio [aPR] = 1.23; 95% confidence interval [CI], 1.05-1.44), condomless sex with multiple female sexual partners (aPR = 1.32; 95% CI, 1.06-1.66), injection drug use (aPR = 3.75; 95% CI, 2.64-5.32), and having sexual partners who were more likely to have ever injected drugs (aPR = 1.84; 95% CI, 1.48-2.28), been incarcerated (aPR = 2.28; 95% CI, 2.01-2.59), or had a concurrent sexual partner (aPR = 1.08; 95% CI, 1.05-1.11), as compared with never-incarcerated men. Conclusions: Incarceration history was associated with HIV risk–related behaviors among heterosexual men from urban areas in the United States. Correctional rehabilitation initiatives are needed to promote strategies that mitigate HIV risk–related behaviors and promote healthy reentry into communities among heterosexual men at high risk for HIV.